Exploring Teachers' Technological and Pedagogical Knowledge: A Case Study in Semarang Excellence School - Kurniasih, Novi (Universitas Negeri Semarang, 2023)
This research aims to illustrate teachers' technological knowledge (TK), pedagogical knowledge (PK), and technological pedagogical knowledge (TPK) as an integral part of TPACK introduced by Koehler and Mishra (2005). The research took place in Semarang Excellence School (SES), specifically in the Olympiad class. By employing a descriptive qualitative approach, the research results indicate that teachers' technological knowledge shows an advanced level of acquisition, particularly regarding the importance of integrating and using technology in learning practices. Likewise, teachers' pedagogical knowledge demonstrates a good level of understanding and practice, mainly because teachers are familiar with a variety of learning methods and techniques and know how to use them appropriately in specific circumstances. Furthermore, teachers' technological pedagogical knowledge, which represents the intersection and accumulation of the two previous domains of teachers' skills, suggests a high level of mastery. For instance, when teachers collaboratively implement conventional and technology-based learning methods and techniques, it enhances student academic achievement in the Olympiad class. Abstrak Penelitian ini bertujuan untuk menggambarkan pengetahuan teknologi (TK), pengetahuan pedagogis (PK), dan pengetahuan pedagogis teknologi (TPK) guru sebagai bagian integral dari TPACK yang diperkenalkan oleh Koehler dan Mishra (2005). Penelitian ini dilakukan di Sekolah Unggulan Semarang (SES), khususnya di kelas Olimpiade. Dengan menggunakan pendekatan deskriptif kualitatif, hasil penelitian menunjukkan bahwa pengetahuan teknologi guru mencapai tingkat kemahiran yang tinggi, terutama dalam hal pentingnya integrasi dan penggunaan teknologi dalam praktik pembelajaran. Begitu pula, pengetahuan pedagogis guru menunjukkan tingkat pemahaman dan praktik yang baik, terutama karena guru mengenal berbagai metode dan teknik pembelajaran serta tahu cara menggunakannya dengan tepat dalam situasi tertentu. Selain itu, pengetahuan pedagogis teknologi guru, yang mewakili persimpangan dan akumulasi dari dua domain keterampilan guru sebelumnya, menunjukkan tingkat penguasaan yang tinggi. Misalnya, ketika guru secara kolaboratif menerapkan metode pembelajaran konvensional dan berbasis teknologi, hal ini dapat meningkatkan prestasi akademik siswa di kelas Olimpiade.